To solve the equation \( 0.2(15x - 20) = 0.5(16 - 2x) \), we will first distribute the constants on both sides.
-
Distributing on the left side: \[ 0.2(15x) - 0.2(20) = 3x - 4 \]
-
Distributing on the right side: \[ 0.5(16) - 0.5(2x) = 8 - x \]
Now we rewrite the equation: \[ 3x - 4 = 8 - x \]
Next, we will add \( x \) to both sides: \[ 3x + x - 4 = 8 \] \[ 4x - 4 = 8 \]
Now, we will add \( 4 \) to both sides: \[ 4x = 12 \]
Dividing both sides by \( 4 \): \[ x = 3 \]
So, the solution is \( \boxed{3} \).